COMPANIES IN THE DATA WAREHOUSE IMPLEMENTATION - Marzuki Marzuki Marzuki (JAKSTIK Journal, 2003)
Data warehouse is a concept and a combination of technologies that facilitate theorganization to manage and maintain historical data obtained from the system or operationalapplications. Data warehouses collect historical data which can then be used as material to becomprehensive for management decisions, organizational needs analysis, through forecastingorganizations based on the data. Data warehouse allows integration of various types of datafrom a variety of applications or systems. This ensures the access mechanism 'one-stop shop'for management to obtain information and analyze it for the decision organizationaldevelopment. Within an organization, data warehouse can be used as weapons in competing.This paper will discuss the implementation of enterprise data warehouse.